Pathogenesis of Enamel-Renal Syndrome Associated Gingival Fibromatosis: A Proteomic Approach - Simancas Escorcia, Victor; Guillou, Clément; Abbad, Lilia; Derrien, Louise; Rodrigues Rezende Costa, Claudio; Cannaya, Vidjea; Benassarou, Mourad; Chatziantoniou, Christos; Berdal, Ariane; Acevedo, Ana Carolina; Cases, Olivier; Cosette, Pascal; et al. (Frontiers in Endocrinology, 2021)
The enamel renal syndrome (ERS) is a rare disorder featured by amelogenesis imperfecta, gingival fibromatosis and nephrocalcinosis. Gingival fibromatosis, a hallmark of the disease is characterized by the accumulation of a collagen-rich, dense connective tissue and of mineral deposits throughout the gingiva. ERS is caused by bi-allelic mutations in the FAM20A Golgi associated secretory pathway pseudokinase (FAM20A) gene encoding a likely allosteric activator of FAM20C, the Golgi associated secretory pathway kinase. How mutations in FAM20A may modify the gingival connective tissue homeostasis and cause fibromatosis is currently unknown. Conditioned media of gingival fibroblasts (GF) obtained from four unrelated ERS patients carrying distinct mutations and three control subjects were used. Secretomic analysis identified 109 dysregulated proteins whose abundance had increased (69 proteins) or decreased (40 proteins) at least 1.5-fold compared to control GF. Gene Ontology (GO) analysis revealed biological processes significantly over-represented or under-represented in the ERS GF. Proteins over-represented were mainly involved in extracellular matrix organization, collagen fibril assembly, and biomineralization whereas those under-represented were extracellular matrix-associated proteins. Accordingly, GO disease analysis indicated a significant enrichment of pathologies such as tumoral angiogenesis and fibrosis. More specifically, ransforming growth factor-beta 2, a member of the TGF-beta family involved in both mineralization and fibrosis was 6.5-fold increased in samples from GF of ERS patients and so were various known targets of the TGF-beta signaling pathway including Collagens, Matrix metallopeptidase 2 and Fibronectin. For the over-expressed proteins quantitative RT-PCR analysis showed increased transcript levels, suggesting increased synthesis. Additional immunohistochemical and western blot analyses showed activation and nuclear localization of the classical TGF-beta effector phospho-Smad3 in steady-state ERS GF. Exposure of these cells to TGFB1 further upregulated the expression of TGF-beta targets suggesting that this pathway could be a central player in the pathogenesis of the ERS gingival fibromatosis. In conclusion our data strongly suggest that TGF-beta-induced modifications of the extracellular matrix contribute to the pathogenesis of ERS. To our knowledge this is the first proteomic-based analysis of FAM20A-associated modifications.